Two distinct Omp85 paralogs in the chloroplast outer envelope membrane are essential for embryogenesis in Arabidopsis thaliana - Hsu, S; Patel, R; Bédard, J; Jarvis, P; Inoue, K (2008)
Homologs of a bacterial β-barrel protein, Omp85, ubiquitously exist in the outer membranes of Gram-negative bacteria, mitochondria and chloroplasts. Those in non-photosynthetic bacteria and mitochondria are responsible for β-barrel protein sorting to the outer membranes, and thus are essential for viability of the organisms. There are two distinct Omp85 homologs in chloroplasts of the model plant, Arabidopsis thaliana. One of them, Toc75, functions as the main protein import translocation channel, and was shown to be indispensable from a very early stage of embryogenesis. By contrast, the role of another homolog, OEP80, remains elusive. Recently, we showed that disruption of the OEP80 gene causes embryo abortion in A. thaliana at a stage later than that affected by TOC75 knockout. This indicates that the two chloroplastic Omp85 homologs are both essential for viability of plants from very early stages of development, but may have distinct functions. Defining the functional and evolutionary relationships of Toc75 and OEP80 by further studies should advance our understanding of the importance of plastids during embryogenesis, as well as that of the molecular details of plastid biogenesis. ©2008 Landes Bioscience.